Styler un document PoPuPS avec LibreOffice - Pochet, Bernard (Presses universitaires de Liège, 2019)
This short manual is mainly intended for editors of PoPuPS journals but can obviously be useful for all Lodel users. Its writing is justified by our choice to recommend, since the use of version 1.0 of Lodel for PoPuPS, to style articles with LibreOffice. It has been built from the help page on Github and on lodel.org, from the house of reviews pages on OpenEdition and from the various emails and help proposed for PoPuPS editors. Written directly inside the e-publish platform of the University of Liege, driven by the PressBooks software, it intends to go completely outside the framework of classical publishing. It is a liquid document that will evolve with time according to the opinions, remarks and questions sent to the author. It has an ISBN number but its publishing date is likely to evolve... don't panic, this is a normal evolution. First work published on the e-publish platform, it also serves as an illustration of the possibilities it offers.